A flexible pressure sensor by induced ordered nano cracks filled with multilayer graphene oxide composite film as a conductive fine-wire network for higher sensitivity. (4th February 2019) - Shi, Jianhao; Bin Sun,; Li, Hongfang; Xia, Kai; Zhang, Xiaojing; Ding, Guifu; Pan, Tingrui; Yang, Zhuoqing
Abstract: Inspired by the structure of skin, a flexible pressure sensor is proposed here, which consists of a flexible Kapton/polydimethylsiloxane (PDMS) substrate, a sensing structural layer of a fine-wire connected conductive network and a protective layer of PDMS. Notably, cracks, often referred to as defects, were utilized to fabricate the conductive network in this work. The ordered nano cracks were induced by changing the temperature of the patterned photoresist film suddenly to form the regular hexagonal array nano-channel network. Then the Ni/multilayer graphene oxide/Ni sandwich composites were introduced to obtain the conductive fine-wire connected network by electroplating and graphene oxide electrodeposition. When the sensor is under pressure, the strain effect of the bottom Ni network, the change of intermediate multilayer graphene oxide microstructure, and the breaks of electron transport paths owing to the top wrinkled Ni cracking, contribute to the resistance change together. As a result, the fabricated flexible pressure sensor shows a maximum sensitivity as high as 4953.15 kPa −1 at 52.27 kPa. In addition, the sensor has a fast response (47 ms) and good repeatability, which are essential for practical applications. Furthermore, the pressure sensor was demonstrated to have good potential in e-skin application, such as pulse detection, laughter and swallowing movement recognition. This work provides a new and convenient approach to fabricate a conductive network with nanowires by induced cracks.